Effect of a single-dose denosumab on mineral homeostasis in infertile men: insights from a pilot intervention study and a randomized controlled trial - Sam Kafai Yahyavi; Rune Holt; Li Juel Mortensen; Ida Marie Boisen; Lív Bech Árting; Anne Jørgensen; Anders Juul; Martin Blomberg Jensen (BMC Medicine, 2025)
Abstract Background Denosumab, a drug that inhibits RANKL to reduce bone resorption in osteoporotic postmenopausal women, has been shown to improve semen quality in a subgroup of infertile men. This study aimed to investigate the effects of denosumab on mineral homeostasis in young infertile men. Methods Secondary data from two clinical trials designed to test the effect on semen quality were used: (1) a pilot intervention study with 12 men receiving a single-dose of 60 mg denosumab and (2) a single-center, double-blinded, randomized clinical trial, where 100 infertile men were randomized 1:1 to receive denosumab 60 mg once sc. or placebo. A linear mixed model for repeated measures was employed to analyze data from follow-up samples. Results In the pilot intervention study, denosumab treatment induced a decrease in ionized calcium 5, 20, 40, and 80 days after treatment compared with baseline (all p < 0.05). Serum phosphate decreased on all time points up to and including day 40 (all p < 0.05), while alkaline phosphatase was only lowered at 40 days and onwards (p = 0.014). Serum PTH increased significantly at all time points up to and including day 80 (p = 0.026). One hundred eighty days after treatment, all reported analyses were comparable to baseline levels. The observed temporal changes were confirmed in the RCT with differences in serum calcium (p < 0.001) and phosphate (p < 0.001) on day 14, PTH (p < 0.002), and alkaline phosphatase (p < 0.001) on days 80 and 160. Denosumab treatment had no significant effect on vitamin D status, renal function, or serum albumin concentration after 80 and 160 days. Conclusions Small but significant changes in mineral homeostasis and bone mineral content were observed but the changes were transient and normalized after treatment cessation. A single injection of denosumab in infertile men appears to have no major long-term impact on bone or mineral homeostasis. Trial registration ClinicalTrials.gov NCT03030196. Registered January 24, 2017.